Microbiological Quality of Community and Animal Drinking Water in and around Mhow, Indore, Madhya Pradesh - Sharma, Supriya; Shivaji Tayde, Ravindra; Kumar, Vipin; Chauhan, Pranav; Rajni (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Microbial contamination of drinking water is a significant public health issue, particularly in developing regions where sufficient sanitation, hygiene, and water treatment are often lacking. This study aimed to assess the microbiological quality of drinking water from various sources with a focus on the presence of Escherichia coli as an indicator of fecal contamination. A total of 240 samples collected in and around Mhow, Indore (MP) (80 each community drinking, packaged water and animal drinking water), were analysed for microbiological quality by multiple tube technique, which displayed MPN (most probable number) indices from <3 to >1100 MPN/100 mL. Based on MPN count, water samples available for human drinking (both community and packaged water combined) were graded as satisfactory (63.75%), suspicious (6.25%) and unsatisfactory (30 %). However, only 0.98% samples graded satisfactory were positive for E. coli. Conversely, 30 % and 35.41% samples observed suspicious and unsatisfactory, respectively, showed the presence of E. coli. In source wise investigation of human drinking water samples, 27.50%, 12.50% and 60.00% community drinking water samples were observed as satisfactory, suspicious and unsatisfactory, respectively, wherein E. coli was detected in 4.54%, 30.00% and 35.41% samples, respectively. On the other hand, all the packaged water samples (100%) were found satisfactory for drinking without presence of E. coli in any of the sample. In the animal drinking water samples, presence of coliforms (100%) including E. coli (31.25 %) found was of considerable concern. High percentage of unsatisfactory water samples with presence of E. coli indicate likely sewage contamination and highlights the urgent need for immediate attention, and action to reduce the risk of water-borne diseases.